Assessment of Genetic Diversity for Seed Quality Parameters in Barley - SUMAN DEVI; YOGENDER KUMAR; AXAY BHUKER; O.P. BISHNOI (Seed Research, 2026)
Fifty genotypes of barley (Hordeum vulgare) were analyzed for genetic divergence on the basis of seed vigour parameters. The observations were recorded on seedling length (cm), seed density (g/cc), standard germination (%), seedling dry weight (mg), vigour index I & II, electrical conductivity (ìS/cm/seed) and accelerated ageing at 40±1ºC for 48 and 72 hours. All the genotypes were grouped into seven well defined clusters depending upon the similarity in the expression of their genetic divergence. Maximum numbers of genotypes were assigned in cluster I (18) followed by cluster IV (12) and V (6), while the cluster II and VII were the smallest one with three genotypes each. Maximum distance among the genotypes within the same cluster was manifested by cluster VII (5.42) followed by cluster II (3.71) and VI (3.63), however the minimum intra-cluster distance was exhibited by the cluster IV (2.23). Cluster VI and VII showed maximum inter-cluster distance of 7.51, followed by cluster II and VI (7.40), whereas it was minimum between cluster I and IV (3.10). Contribution of electrical conductivity towards divergence was maximum (32.24%) thereafter accelerated ageing (72 h and 48 h) which contributed 18.78% and 17.71%, respectively. The clusters II and III were composed of highly vigorous genotypes (IBYT-HI-17, 2ndGSBYT-02 (2015), BH 15-17, RD 2909, 2nd GSBYT-23 (2015), 2nd GSBSN-28 (2015), MGL-117) because of better cluster means for most of the traits studied. Therefore, genotypes of clusters II and III might be considered as promising parents for barley improvement programme.